(untitled) (PUSA Journal of Hospitality and Applied Sciences, 2016)
Background: Women constitute an important labour force in all the countries. Nearly 1/3rd of our labour force [32%] consists of women. Working women constitute 16.43% of the female population of the country. The main problem with these female workers is that they are harassed in work place in different ways. Objective: Unveil the challenges, problems and difficulties confronted by women at their work place as well as at their home due to their profession. Method: The study was conducted on seventy eight women working in the hospitality industry and data was collected through questionnaires. Results: The paper derives its findings from observations & questionnaires & feedback forms collected from women professionals of the hospitality industry is that the women are facing is gender discrimination. Conclusion : The society should undersatnd that today’s women are countributing to the ecomomic development of the country and not look the upon as an inferior creature.